A Systematic Approach to Innovative Strategies for Vocal Instruction in Higher Education: Enhancing Student Performance - Du, Qiusheng (Pacific International Journal, 2024)
This study presents a systematic approach to developing innovative strategies for vocal instruction in higher education, focusing on enhancing student performance. Using Huaiyin Normal University as a case study, the research examines current vocal instruction practices within its Music Department, identifying both strengths and areas needing improvement. The study first provides an overview of traditional and contemporary pedagogical approaches, highlighting the importance of student-centered learning and the integration of technology in music education. Data were collected through interviews with vocal instructors and surveys with students to analyze the effectiveness of existing methods and the feedback from those directly involved. Key findings reveal a need for greater incorporation of collaborative learning, multicultural repertoires, and personalized vocal techniques to foster a more engaging and comprehensive learning environment. The study discusses the implications of these findings for higher education in music and compares them with practices at other institutions. It also addresses the challenges faced in implementing innovative strategies and provides practical recommendations for curriculum development. This research contributes to the broader discourse on enhancing vocal education through adaptive, inclusive, and modernized teaching practices.